(3GdJMOjGJ GdJj JhGLg efXeGJ GdGYeGd GdeYGUQI (B:s (3GdCReI GdeGdjI hGdYGdejI hGdCaGb GdeSJbHdjI (B/s - (3GdUejOYj, eMehOs; (3GdYHGOj, SejQs ((3YeGf(B: s (3ecJHI GdeLJeY GdYQHj(B, s, 2011)
(3CgejI GdQbGHI GdOGNdjI dfXe GdeYdheGJ GdeMGSHjI h OhQgG aj JMbjb Cef GdeYdheGJ aj Xd HjFI GdJLGQI GdGdcJQhfjI , GdGWGQ GdeaGgjej dHfGA fehPL ebJQM dGOGQI YdGbI GdRHhf aj GdbWGY GdNOej , OhQ GdeYQaI GdJShjbjI aj ehGLgI GdCReGJ GdJShjbjI aj GdTQcGJ GdUfGYjI GdeSGgeI GdYGeI GdGQOfjI , CKQ MLe GdTQcI h MLe GdeHjYGJ h MLe GdGSJKeGQ GdGLfHj Ydi GdGaUGM Yf GdeSDhdjI GdGLJeGYjI (B: (3OQGSI MGdI GdTQcGJ GdUfGYjI GdeOQLI aj HhQUI YeGf dYGe (B2007 (3, GdGNdGbjGJ h GfYcGSgG Ydi HMhK GdJShjb aj efXeGJ GdGYeGd , OhQ GdeRjL GdJQhjLj GdCeKd aj feh GdMUI GdShbjI ddTQcGJ GdUfGYjI GdGQOfjI (B: (3OQGSI MGdI , fXe GdeYdheGJ GdJShjbjI h OhQgG aj GOGQI GdCReGJ GdJShjbjI , CKQ GdGReI GdYGdejI Ydi GdCSGdjH GdJQhjLjI ddUGOQGJ GdCQOfjI , GdCReI GdeGdjI GdYGdejI (B: (3GJLGgGJ GdJTHg HGdfXGe GdeGdj GdGSdGej , CReI GdQgf GdYbGQj h GdGReI GdeGdjI GdYGdejI , Jehjd h GOGQI GdbQV GdYbGQj (B: (3QDjI GSdGejI MOjKI , GKQ GdGReI GdeGdjI GdYGdejI Ydi TQcGJ GdJCejf GdYQHjI , hGbY UfGOjb GdKQhI GdSjGOjI GdYQHjI aj Xd CReI GdQgf GdYbGQj (B.s
Keywords: (3GdGReGJ GdGbJUGOjIs; (3GdJShjbs; (3GdeGdjIs; (3GdeMGSHIs